Meaningful engagement of new scholars at international seminars: communities of practice as a pathway. Issue 1 (2nd January 2020) - Groen, Janet; Roy, Sylvie
ABSTRACT: In this paper, two professors in education share their reflections on their experience designing and implementing an International Doctoral Research Seminar at their university. Using a collaborative autoethnographic methodology, they consider how such seminars have the potential to provide space for emerging academics to actively engage and learn from each other in authentic and meaningful ways. Using communities of practice and transcultural pedagogies frameworks, the authors unpack the dynamics of this particular seminar, drawing on their respective reflections regarding the design and animation of this experience. Authors refer to the significance of creating a caring and open community through all phases of the seminar and mindfully cultivating a learning space that works toward creating a more inclusive and active learning culture As the authors advance implications for practice they draw on a transcultural discourse with its emphasis on engagement with other cultures in order to move beyond one's cultural and language of origin, toward the integration of different views.